PENANAMAN NILAI AKHLAK MELALUI METODE BERCERITA PADA SISWA DI TK ISLAM AL-ABRAR PAKAN SINAYAN KEC. BANUHAMPU KAB. AGAM - Muhamad Iqbal; Deswalantri Deswalantri; Jasmienti Jasmienti; Darul Ilmi (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of this research is that students tend to find their own fun such as telling stories with friends, doodling on books and also during the process and constantly asking for garden play. The goal to be achieved in this study is to find out the teacher's technique in instilling values ​​through the storytelling method. The type of research used is descriptive qualitative. The key informants are Al-Abrard Islamic Kindergarten teachers and the supporting informants are students and parents. The data collection methods are interviews, observation and documentation. Data analysis techniques used to examine all data, data reduction and data display. The results of the study revealed that the way teachers instill moral values ​​include learning to pray, getting children to say greetings, getting children to help and working together, getting children to always maintain cleanliness, getting children to speak politely, getting children to respect and appreciate each other. , train children to use their right hand when giving and receive something, prepare children not to leave class without permission, get children to say thank you. The teacher's methods in applying techniques include reading directly from story books, using illustrated pictures from books, telling fairy tales, using flannel boards, using puppet media, dramatizing a story. Keywords: Cultivating Moral Values ​​and Storytelling Method Techniques